2009
DOI: 10.1111/j.1471-4159.2009.06087.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting astrocytic activation: a novel analgesic mechanism of ketamine at the spinal level?

Abstract: Although ketamine is widely used as an analgesic agent and has an anti‐allodynic effect on neuropathic pain, the underlying analgesic mechanisms are not fully explained by the modern ‘neuronal‐based’ theories. As emerging studies have focused on the critical role of spinal astrocytes in the pathological pain states, we have hypothesized that there exist some ‘astrocytes‐related’ mechanisms in the analgesic function of ketamine. In the present study, using the spinal nerve ligation (SNL) pain model, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 54 publications
5
28
0
Order By: Relevance
“…The dosages of ketamine and poly I:C used in the present study were in accordance with previous research [2,21,32] and our pilot experiment.…”
Section: Intrathecal Implantation and Drug Administrationsupporting
confidence: 57%
“…The dosages of ketamine and poly I:C used in the present study were in accordance with previous research [2,21,32] and our pilot experiment.…”
Section: Intrathecal Implantation and Drug Administrationsupporting
confidence: 57%
“…As observed in our previous study, inhibiting astrocytic activation is probably a novel analgesic mechanism of ketamine [37]. Some opioid receptors (μ, κ and δ subtypes) and toll like receptors (TLRs) are expressed on astrocytes.…”
Section: Discussionmentioning
confidence: 73%
“…Drugs and normal saline were injected intrathecally over 30 s, followed by a 10 μl flush of normal saline. The dosages of ketamine used in the present study were chosen based on previous research [18,21] and pilot experiments.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have been carried out to elucidate the mechanisms underlying this analgesic effect, but without satisfying output. Previous study [21] showed that both intraperitoneal and intrathecal ketamine inhibit SNL-induced allodynia; however, intrathecal but not intraperitoneal ketamine suppresses SNL-induced astrocytic activation as reflected by down-regulated glial fibrillary acidic protein (GFAP) expression. These results suggest that intraperitoneal ketamine could alleviate SNL-induced neuropathic pain via classical "neuronal-based" mechanisms but, in addition, "astrocyte-related" mechanisms may also be important in underlying the anti-allodynic effect of intrathecal ketamine.…”
Section: Introductionmentioning
confidence: 99%